Rehabilitative Punishment and the Drug Treatment Court Movement - Boldt, Richard C. (1998)
Part I of this Article briefly summarizes the history of rehabilitative penal practice in the United States during the twentieth century. The discussion pays special attention to the sustained critique of the rehabilitative ideal offered by left-liberal commentators twenty-five to thirty years ago. The discussion analyzes particular shortcomings that plagued corrections practices at this earlier juncture and explores the relevance of that history to today's drug treatment courts. Part II builds on the observation of the left-liberal critics that rehabilitative penal regimes, by blending punitive and therapeutic impulses, often seek to accomplish incompatible goals. This Part suggests that this conflict in objectives manifests itself predominantly in the tension between the norms of adversary adjudication that characterize traditional criminal law practice and the procedural informality and judicial activism that characterize rehabilitative undertakings. The consequences of this tension for defendants are illuminated by examining the role conflicts faced by their attorneys in these settings. This general discussion regarding the distorting effect that rehabilitative penal practice has on defender role also includes a more particular analysis of the special problems facing defense attorneys and, by extension, their clients in drug treatment courts. Part III examines a similar set of departures from traditional adversarial adjudication in the context of juvenile court proceedings. The analogy between drug treatment courts and juvenile courts is useful because attorney role problems associated with procedural informality have received extensive scholarly discussion in the juvenile court area. Part III then reviews some of the most relevant literature from that area, giving particular attention to several of the more thoughtful proposals offered for guiding defense attorneys in the formulation of an appropriate role conception. This discussion concludes by arguing that these accounts of attorney role in the juvenile court context do not adequately address the problems faced by defense counsel in drug treatment courts. Finally, Part IV evaluates whether defense attorneys in drug treatment court can practice in a way that responds to the enduring insights of the left liberal critics of the rehabilitative ideal. This Part offers a role conception formulated by reference to the critics' assertion that rehabilitative processes are often morally suspect, because they undermine defendants' dignity interests, obscure the unique perspective of those who are the objects of coercive treatment, and deteriorate into unalloyed punishment. Part IV examines several concrete measures designed to guard against these dangers, particularly by paying specific attention to the special needs of defendants suffering from addiction. Part IV concludes that these minimum requirements for responsible defense practice in drug treatment courts are unlikely to be met on a consistent basis